2022
DOI: 10.1128/aac.00540-22
|View full text |Cite
|
Sign up to set email alerts
|

Roseoflavin, a Natural Riboflavin Analogue, Possesses In Vitro and In Vivo Antiplasmodial Activity

Abstract: The ability of the human malaria parasite Plasmodium falciparum to access and utilize vital nutrients is critical to its growth and proliferation. Molecules that interfere with these processes could potentially serve as antimalarials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…To investigate whether the RoF resistant parasites were cross-resistant to 8AF, we determined the sensitivity of the resistant parasites to 8AF. As the solubility of 8AF only permits testing up to 50 µM, we assessed the sensitivity in riboflavin-free RPMI where the IC 50 against WT parasites is 2 ± 0.4 nM rather than complete RPMI where the IC 50 of 8AF is 7 ± 1 µM 16 . The IC 50 values of 8AF in riboflavin-free medium against the RoF-A-E8, RoF-A-B6, RoF-B-E11, RoF-B-G2 parasite lines (1.2 ± 0.1 µM, 1.1 ± 0.1 µM, 1.2 ± 0.1 µM, 1.1 ± 0.1 µM, respectively) were found to be 1000-fold higher than those of the parent strain (0.0010 ± 0.0002 µM, P<0.0001, unpaired t-test; Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate whether the RoF resistant parasites were cross-resistant to 8AF, we determined the sensitivity of the resistant parasites to 8AF. As the solubility of 8AF only permits testing up to 50 µM, we assessed the sensitivity in riboflavin-free RPMI where the IC 50 against WT parasites is 2 ± 0.4 nM rather than complete RPMI where the IC 50 of 8AF is 7 ± 1 µM 16 . The IC 50 values of 8AF in riboflavin-free medium against the RoF-A-E8, RoF-A-B6, RoF-B-E11, RoF-B-G2 parasite lines (1.2 ± 0.1 µM, 1.1 ± 0.1 µM, 1.2 ± 0.1 µM, 1.1 ± 0.1 µM, respectively) were found to be 1000-fold higher than those of the parent strain (0.0010 ± 0.0002 µM, P<0.0001, unpaired t-test; Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Although we have recently shown that the parasite is capable of FMN and FAD synthesis 16 , the putative P. falciparum flavokinase gene remained to be experimentally verified and characterised. In this study, present data consistent with the putative Pf FK gene coding for a monofunctional flavokinase that utilises riboflavin, RoF and 8AF as substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these promising aspects, researchers have investigated these pathways to inhibit microbes. Recently, roseoflavin, a riboflavin analogue, was found to inhibit the proliferation of the malaria parasite [ 50 ]. Also, riboflavin synthase was selected as a therapeutic target to inhibit gut microbes involved in the development of colorectal cancer [ 51 ].…”
Section: Vitamin Biosynthesis As a Drug Target For New Antibioticsmentioning
confidence: 99%